Tourism Recovery Scorecard (TOURS) – Benchmarking and monitoring progress on disaster recovery in tourism destinations. (March 2018) - Khazai, Bijan; Mahdavian, Farnaz; Platt, Stephen
Abstract: After a disaster, tourism declines and tourist stakeholders suffer because tourists cancel their reservations and choose to go elsewhere. A key part of managing recovery of tourism destinations is restoring the destination image and reputation which can be affected by negative or inaccurate media coverage. This paper reports the results of surveys with tourism sector stakeholders aimed at measuring recovery in three tourism destinations affected by two back-to-back disasters: the Bohol earthquake and tropical cyclone Haiyan in 2013 in the Philippines. The authors developed a methodological framework for the Tourism Recovery Scorecard (TOURS), which can be used as a crisis communication tool for benchmarking and monitoring progress on post disaster recovery of a tourism destination. Three main dimensions of safety, physical recovery and business recovery are considered in the Scorecard, each containing key factors that are important to tourists and meaningful to tourism operators.